Spectrum of neuropsychological challenges in Turner syndrome - Fezza, Jacqueline I.; Rau, Srishti; Clary, Lauren; Nimene Johnson, Oretha; Fimmel, Fiona; Barber, John; Kanakatti Shankar, Roopa (Frontiers in Endocrinology, 2024)
Turner syndrome (TS) is associated with significant neuropsychological challenges and screening is recommended at key transition stages. Our goal was to describe the institutional experience of formal neuropsychological assessments in TS and assess differences by karyotype. Data were abstracted by retrospective chart review of completed assessments between 01/01/2019 -10/31/2022 referred from the newly established multidisciplinary clinic and descriptive statistical analyses are presented (SAS V9.4). Of 114 patients, 38 (33%) had completed neuropsychological assessment at a median age 11.3 years (IQR 6.5-14.9). Median full-scale IQ (FSIQ) was lower in those with 45,X karyotype compared with other karyotypes (p=0.027), but did not meet statistical significance at the adjusted significance level for multiple comparisons. Lower median non-verbal IQ (PIQ) relative to verbal IQ (VIQ) was observed. Diagnoses of ADHD (26%), anxiety disorder (26%), were common followed by specific learning disorder (mathematics; 18%) and autism spectrum disorder (16%). The prevalence of neuropsychological abnormalities in our diverse clinic underscores the importance of early and routine neuropsychological testing in TS.